Educational mobility in transition: what can China and the UK learn from each other?. Issue 6 (10th July 2017) - Quan, Rose; Pearce, Alison; Baranchenko, Yevhen
Abstract : Purpose: The purpose of this paper is to explore the differences in international student mobility (SM) in two contrasting countries: UK and China, at national, institutional and individual levels. Both are countries in transition in a greater global context. The objective is to identify what these countries can learn from each other about the issues and policies surrounding the management of educational mobility. Design/methodology/approach: An inductive approach was employed to understand real-life experience via multiple case studies. Participant observation and semi-structured interview methods with a variety of stakeholders were used to collect data which were then subjected to a thematic analysis to identify in which areas countries had developed good practice. Findings: Over-arching themes were developed through comparing national findings. These reveal that national policy and family support are most influential in China, while British universities largely drive SM at an institutional level. Social implications: The significance of this knowledge lies in the potential for social impact and reform of successful mobility schemes. International mobility equates to social mobility through global employability of those who engage. Global citizenship is regarded as one of the paths to world peace and understanding. Mobilising a younger generation can contribute to better regional integration and international stability as part of an idealistic approach to geopolitics. Originality/value: Concluding that neither country has a comprehensive and complete approach, this study proposes the areas in which all both could develop and details good practice. The value therefore emerges from the comparison and contrast and the practical focus of the research.